DC Subsets Regulate Humoral Immune Responses by Supporting the Differentiation of Distinct Tfh Cells - Bouteau, Aurélie; Kervevan, Jérôme; Su, Qingtai; Zurawski, Sandra M.; Contreras, Vanessa; Dereuddre-Bosquet, Nathalie; Le Grand, Roger; Zurawski, Gerard; Cardinaud, Sylvain; Levy, Yves; Igyártó, Botond Z. (Frontiers in Immunology, 2019)
To determine the contribution of skin DC subsets in the regulation of humoral immunity, we used a well-characterized antigen targeting system to limit antigen availability and presentation to certain skin-derived DC subsets. Here we show that delivery of foreign antigen to steady state Langerhans cells (LCs) and cDC1s through the same receptor (Langerin) led to, respectively, robust vs. minimal-to-null humoral immune response. LCs, unlike cDC1s, supported the formation of germinal center T follicular helper cells (GC-Tfh) antigen dose-dependently and then, likely licensed by these T cells, some of the LCs migrated to the B cell area to initiate B cell responses. Furthermore, we found that the cDC1s, probably through their superior T cell activation capacity, prevented the LCs from inducing GC-Tfh cells and humoral immune responses. We further show that targeted delivery of cytokines to DCs can be used to modulate DC-induced humoral immune responses, which has important therapeutic potential. Finally, we show that human LCs, unlike monocyte-derived DCs, can support GC Tfh generation in an in vitro autologous system; and in agreement with mouse data, we provide evidence in NHP studies that targeting LCs without adjuvants is an effective way to induce antibody responses, but does not trigger CD8+ T cell responses. Our findings suggest that the major limitations of some relatively ineffective vaccines currently in use or in development might be that (1) they are not formulated to specifically target a certain subset of DCs and/or (2) the antigen dose is not tailored to maximize the intrinsic/pre-programmed capabilities of the specific DC subset. This new and substantial departure from the status quo is expected to overcome problems that have hindered our ability to generate effective vaccines against some key pathogens.